2012
DOI: 10.1002/ange.201201281
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X‐ray Structural Studies of a Flexible Host Responding to Incremental Gas Loading

Abstract: Crystallographic pressure‐lapse snapshots of a porous material responding to gas loading were used to investigate the stepwise uptake of carbon dioxide and acetylene molecules into discrete confined spaces. Based on the data, a qualitative statistical mechanical model was devised that reproduces even subtle features in the experimental gas sorption isotherms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Atwood, Barbour et al have shown that nonporous crystals of p-tert-butylcalix [4]arene can uptake guests by cooperative van der Waals confinement. 18 Barbour has also reported that an apparently nonporous crystalline lattice of a metallacycle can absorb gaseous guests, 19 and Cooper has demonstrated that Xe and Ra can diffuse through a robust lattice of organic cages despite windows between the cage pores being smaller than the diameter of the gases. 20 Interestingly, preliminary experiments also showed a moderate uptake of Xe by complex 2•6(BF 4 ), which was more pronounced than uptake of the smaller Kr (see SI).…”
mentioning
confidence: 99%
“…Atwood, Barbour et al have shown that nonporous crystals of p-tert-butylcalix [4]arene can uptake guests by cooperative van der Waals confinement. 18 Barbour has also reported that an apparently nonporous crystalline lattice of a metallacycle can absorb gaseous guests, 19 and Cooper has demonstrated that Xe and Ra can diffuse through a robust lattice of organic cages despite windows between the cage pores being smaller than the diameter of the gases. 20 Interestingly, preliminary experiments also showed a moderate uptake of Xe by complex 2•6(BF 4 ), which was more pronounced than uptake of the smaller Kr (see SI).…”
mentioning
confidence: 99%
“…For 1b, 1b_15 bar, or 1b_20 bar the crystal was mounted on a glass fiber inside an environmental gas cell. 35,42 Prior to data collection the gas cell was evacuated at ∼2 × 10 −3 mbar for 12 h to remove any potential traces of guest molecules or adsorbed water vapor. The crystal was then subjected to pressures of 15 bar (1b_15 bar) and 20 bar (1b_20 bar), and the data were collected for each of these pressures.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…29−39 Given the difficulty in maintaining crystal singularity for desolvated flexible/dynamic MOFs under high pressures and ambient temperatures, the studies to monitor their structural transformations have exclusively relied on in situ powder crystal X-ray diffraction (PXRD) tools, which however cannot provide unequivocal structural information as in situ single-crystal X-ray diffraction (SCXRD) experiments can. 19,35,36 This makes it even more challenging to crystallographically identify the binding sites of gas molecules within flexible/dynamic MOFs, which thus far are elucidated mainly through computational studies. 8,13,14,16,25 In this contribution, we report a flexible three-dimensional (3D) microporous cadmium(II) MOF (Cd-MOF) with 4-fold interpenetration and diamondoid (dia) topology, which after desolvation shows an interesting "gating effect" process and "breathing" behavior upon CO 2 sorption.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have shown that the guest molecules in metallocycles can be removed to yield the guest-free (apohost) structure and that guest-exchange processes can occur in a single-crystal to single-crystal (SC− SC) manner. 11,12 Studies of the sorption and separation of solvents (in liquid or vapor form) and gaseous molecules are abundant in the literature. 13−16 In contrast, very few studies have been reported that involve the sorption of vapors of solids.…”
Section: ■ Introductionmentioning
confidence: 99%